x2-5x-4=0

Use the quadratic formula to find the solutions.

-b±b2-4(ac)2a

Substitute the values a=1, b=-5, and c=-4 into the quadratic formula and solve for x.

5±(-5)2-4⋅(1⋅-4)2⋅1

Simplify the numerator.

Raise -5 to the power of 2.

x=5±25-4⋅(1⋅-4)2⋅1

Multiply -4 by 1.

x=5±25-4⋅-42⋅1

Multiply -4 by -4.

x=5±25+162⋅1

Add 25 and 16.

x=5±412⋅1

x=5±412⋅1

Multiply 2 by 1.

x=5±412

x=5±412

Simplify the numerator.

Raise -5 to the power of 2.

x=5±25-4⋅(1⋅-4)2⋅1

Multiply -4 by 1.

x=5±25-4⋅-42⋅1

Multiply -4 by -4.

x=5±25+162⋅1

Add 25 and 16.

x=5±412⋅1

x=5±412⋅1

Multiply 2 by 1.

x=5±412

Change the ± to +.

x=5+412

x=5+412

Simplify the numerator.

Raise -5 to the power of 2.

x=5±25-4⋅(1⋅-4)2⋅1

Multiply -4 by 1.

x=5±25-4⋅-42⋅1

Multiply -4 by -4.

x=5±25+162⋅1

Add 25 and 16.

x=5±412⋅1

x=5±412⋅1

Multiply 2 by 1.

x=5±412

Change the ± to -.

x=5-412

x=5-412

The final answer is the combination of both solutions.

x=5+412,5-412

The result can be shown in multiple forms.

Exact Form:

x=5+412,5-412

Decimal Form:

x=5.70156211…,-0.70156211…

Solve using the Square Root Property x^2-5x-4=0